2022
DOI: 10.3389/fnut.2022.859627
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extensively Hydrolyzed Infant Formula on Circulating Lipids During Early Life

Abstract: BackgroundCurrent evidence suggests that the composition of infant formula (IF) affects the gut microbiome, intestinal function, and immune responses during infancy. However, the impact of IF on circulating lipid profiles in infants is still poorly understood. The objectives of this study were to (1) investigate how extensively hydrolyzed IF impacts serum lipidome compared to conventional formula and (2) to associate changes in circulatory lipids with gastrointestinal biomarkers including intestinal permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Bibliometric analyses of clinical lipidomics publications in 2022 according to separation techniques, detectors, and RPLC columns used …”
Section: In Review: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bibliometric analyses of clinical lipidomics publications in 2022 according to separation techniques, detectors, and RPLC columns used …”
Section: In Review: Materials and Methodsmentioning
confidence: 99%
“…Bibliometric analyses of clinical lipidomics publications in 2022 using Scopus search terms “lipidomics” AND “clinic*” on 15 th December 2022 …”
Section: In Review: Materials and Methodsmentioning
confidence: 99%
“…The type of infant feeding, i.e., breastfeeding vs. formula feeding, has also a profound impact on infant lipidome as well as on the gut microbiome, intestinal function, and immune function [16]. Recent study investigated whether infant formula in which the protein content was modified by hydrolyzation of the proteins to smaller peptides is beneficial to the standard cow's milk formula extensively hydrolyzed milk formula [17]. This study revealed that the type of formula had a major impact on the infants' longitudinal lipidomic profiles, with higher level of sphingomyelins in the hydrolyzed formula-fed group.…”
Section: Lipidomics Changes In Undernutrition and In Early Lifementioning
confidence: 99%